2011
DOI: 10.1111/j.1365-2893.2011.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography for predicting clinical outcomes in patients with chronic liver disease

Abstract: There is increasing interest in developing noninvasive means to evaluate liver fibrosis in patients with chronic liver disease to determine disease severity, prognosis and optimal treatment. Transient elastography (TE) has previously been demonstrated to predict the presence or absence of advanced fibrosis. The current study was conducted to determine whether TE can identify patients with chronic liver disease at risk of clinical decompensation. A total of 667 patients underwent TE and were followed for a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 33 publications
7
43
0
Order By: Relevance
“…Among these patients, cirrhosis had not been suspected or the patients had refused to undergo liver biopsy. Our present rates of complications (12.7/100 PY) and liver-related deaths (0.6/100 PY) were comparable to those previously reported in both LSM-based and biopsy-based studies, in which decompensation has been reported as 5–12/100 PY and liver-related mortality as 1/100 PY [18], [28][31]. We observed few liver-related complications among hepatitis B patients; however, due to the low number of events, the incidence was not statistically different from that among hepatitis C patients.…”
Section: Discussionsupporting
confidence: 90%
“…Among these patients, cirrhosis had not been suspected or the patients had refused to undergo liver biopsy. Our present rates of complications (12.7/100 PY) and liver-related deaths (0.6/100 PY) were comparable to those previously reported in both LSM-based and biopsy-based studies, in which decompensation has been reported as 5–12/100 PY and liver-related mortality as 1/100 PY [18], [28][31]. We observed few liver-related complications among hepatitis B patients; however, due to the low number of events, the incidence was not statistically different from that among hepatitis C patients.…”
Section: Discussionsupporting
confidence: 90%
“…Since repeated liver biopsy is not feasible to provide information on clinical progression of cirrhosis and is not favored by patients and HVPG measurement is not routinely performed in every center, several noninvasive methods have been developed to substitute these invasive procedures, among those several serum biomarkers [7] or measurement of LS by TE [8]. The potential of TE for assessment of the degree of liver fibrosis has been extensively studied in different forms of chronic liver disease [8][9][10][11][12], in this context TE may also provide prognostic information [13,14]. An additional application of TE for identifying patients with portal hypertension or with gastroesophageal varices has been suggested in several other studies [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic capacity of TE has been evaluated in patients with chronic liver diseases of varying etiologies [9, 25–27], in compensated HCV-related liver cirrhosis with or without human immunodeficiency virus (HIV)-coinfection [28–31], and in liver transplantation [32]. All of these studies reported a good ability of TE for the identification of clinical outcomes including liver-related events (LRE) [9, 26, 27, 29–31], death [26, 30, 33], hepatocellular carcinoma [28], and composite endpoints [25]. However, no validated prediction model based on TE has been developed for LRE in patients with chronic hepatitis C with or without cirrhosis, and very little is known about TE cutoffs for stratification of the risk of LRE.…”
mentioning
confidence: 99%